KAJIAN PEMANFAATAN RUANG PADA KAWASAN LINDUNG DI KOTA MANADO (STUDI KASUS: KECAMATAN MAPANGET) - Pangauw, Kindly Anugerah Imanuel; Dariwu, Claudia Talita; Pangalila, Fiska Chintya Ezra (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Mapanget District, as a new growth center in Manado City, faces significant challenges in controlling spatial utilization, particularly within its protected areas. The dynamics of rapid economic and population growth have triggered land-use changes that are often inconsistent with the Spatial Plan (RTRW), potentially leading to environmental degradation and a decline in spatial quality. This study aims to assess the level of suitability between existing spatial utilization and the spatial pattern plan for protected areas in Mapanget District. The primary focus is to identify the extent and distribution of non-compliant locations and to analyze the contributing factors to provide a basis for government recommendations. The research employed a quantitative approach with an overlay analysis method using ArcGIS 10.8 software. Spatial data from the 2023-2042 Manado City Spatial Plan were overlaid with existing land use data from 2024, updated via satellite imagery. The analysis revealed a very high level of non-compliance: of the total 233.17 hectares of protected areas analyzed, 169.80 hectares (72.8%) were found to be inconsistent with the spatial pattern plan, while only 63.37 hectares (27.2%) were compliant. The most significant non-compliance was identified in areas designated as Green Open Space (RTH), such as District Parks and Cemeteries, which are now dominated by mixed-crop plantations (150.85 hectares) and built-up areas like settlements. In conclusion, there is an urgent need for the Manado City Government to evaluate and strengthen the enforcement of spatial planning regulations through more effective supervision, law enforcement actions, and the prioritization of land acquisition programs to secure the function of protected areas from massive land-use conversion. ABSTRAKKecamatan Mapanget, sebagai pusat pertumbuhan baru di Kota Manado, menghadapi tantangan signifikan dalam pengendalian pemanfaatan ruang, khususnya di kawasan lindung. Dinamika pertumbuhan ekonomi dan penduduk yang pesat memicu alih fungsi lahan yang seringkali tidak sejalan dengan Rencana Tata Ruang Wilayah (RTRW), sehingga berpotensi merusak lingkungan dan menurunkan kualitas ruang. Penelitian ini bertujuan untuk mengkaji tingkat kesesuaian antara pemanfaatan ruang eksisting dengan rencana pola ruang pada kawasan lindung di Kecamatan Mapanget. Fokus utama adalah untuk mengidentifikasi luasan dan sebaran lokasi yang tidak sesuai serta menganalisis faktor-faktor penyebabnya sebagai dasar rekomendasi bagi pemerintah. Metode yang digunakan adalah pendekatan kuantitatif dengan analisis tumpang susun (overlay) menggunakan software ArcGIS 10.8. Data spasial rencana pola ruang RTRW Kota Manado Tahun 2023-2042 ditumpangsusunkan dengan data penggunaan lahan eksisting tahun 2024 yang diperbaharui melalui citra satelit. Hasil analisis menunjukkan tingkat ketidaksesuaian yang sangat tinggi, di mana dari total 233,17 hektar kawasan lindung yang dianalisis, sebesar 169,80 hektar (72,8%) tidak sesuai dengan rencana pola ruang, dan hanya 63,37 hektar (27,2%) yang telah sesuai. Ketidaksesuaian terbesar ditemukan pada lahan yang direncanakan sebagai Ruang Terbuka Hijau (RTH), seperti Taman Kecamatan dan Pemakaman, yang kini didominasi oleh Kebun Campuran (150,85 hektar) serta kawasan terbangun seperti permukiman. Kesimpulannya, terdapat urgensi bagi Pemerintah Kota Manado untuk mengevaluasi dan memperkuat penegakan regulasi tata ruang melalui pengawasan yang lebih efektif, penertiban, dan prioritas pada program pengadaan tanah untuk mengamankan fungsi kawasan lindung dari alih fungsi lahan yang masif.